WBS-Pareto-ABC and CPI Model for Pre-Construction Cost Control of A-KRIS Hospital Building - Endah Atika; Hermawan Hermawan; Hidayatus Sibyan (Program Studi Teknik Sipil Sekolah Tinggi Teknologi Pekanbaru, 2026)
Pre-construction cost control in hospital ward completion projects requires a systematic approach capable of identifying cost concentration before construction begins because healthcare rehabilitation works involve complex interations among MEP-HVAC, sanitation, air-conditioning systems and functional building components. This study aims to develop a novel pre-construction cost control framework by integrating the Work Breakdown Structure (WBS), Pareto-ABC analysis, Area Cost Index (ACI) and a newly proposed Control Priority Index (CPI) for the A-KRIS Hospital Building completion project at RSUD Hj. Anna Lasmanah Banjarnegara. A quantitative descriptive case study was conducted through Bill of Quantity (BoQ) validation, WBS mapping, cost aggregation by work zone and sub-work, area cost index calculation, Pareto-ABC classification, and CPI formulation. The project cost was IDR 930,571,644 (including 11% VAT), with an area cost index of IDR 606,093/m2. Cost distribution was highly concentrated in Teratai Ward (60.18%) and Soka Ward (39.10%) accounted for 78.78% of the total project cost. The proposed CPI further differentiates priority among high-cost work items by integrating cost contribution, zone dominance, ABC classification, and optional technical risk, enabling more targeted prioritization of AHU isolation, air-conditioning, sanitation, piping, aluminium works and nurse station components. Unlike conventional Pareto-ABC analysis, which prioritizes work items solely based on cumulative cost, the proposed WBS-Pareto-ABC-CPI framework provides a structured decision-support model that links cost concentration with managerial control priorities during the pre-construction stage. The framework contributes to construction management by transforming conventional BoQ data into a practical and replicable tool for preventive cost, procurement, quality, schedule and safety control that can be applied tohospital rehabilitazion and other public-building projects.